A identidade lexical de Cláudio, Minas Gerais: uma análise sociolinguística - Juraci da Silva Carmo (2024)
Words perform a central role in the functioning of a language when they present thesocial,cultural, historical and political changes of a people and they are the essencefor thereconstruction of an era. The lexicon of a language has been constantly renewed, alwaysadapting to the changes that society experiences. Therefore, it is common for lexical variationto end up becoming quite noticeable even to those less attentive. The formalizationofscientific studies that analyze lexical variations has been, however, arousing the interest ofresearchers for some time. Proof of that is the work undertaken by Amaral (1920), or theonedeveloped by Ribeiro et al. (1977). In addition, more recent works such as those carriedoutby Souza (2008), Ribeiro (2010), Freitas (2012), Cordeiro (2013), Miranda (2015) approachlexical variation as a central element. This study, such as the works aforementioned, haslexical variation as its main interest. The study sought to describe, analyze andrecordthelexical choices of inhabitants from Cláudio, a town located in the center-western regionoftheState of Minas Gerais. The town, whose population is of 30,159 people, has foundryandmetallurgy as its main economic industries. Agriculture and livestock farmingare,nevertheless, also very relevant in that town. Considering that among the theoreticalframework adopted by this research are the Theory of Linguistic Variation andChangeproposed by Labov (2008 [1972]) and Weinreich, Labov and Herzog (2006 [1968]), aswellas Milroy’s notions of social networks (1987) and Milroy (1992), the analyses werecarriedout by taking into consideration that the social profile of each one of the speakerstobeinterviewed should be traced to understand their lexical choices. This procedure evinced, forinstance, that it is quite common for terms used by rural workers to be taken by thosespeakersto extra-work communicative situations - such as moments of leisure - and this causesthelexicon to be expanded by those speakers. Furthermore, the definitions of basic issuestobeconsidered when developing a dictionary, presented by Haensch et al. (1982); Barbosa(1980)and (2001) were extremely important towards creating lexicographic sheets anda glossarywith the 158 words and 33 complex units of the lexicon extracted frominterviews performedwith speakers of Cláudio, Minas Gerais. Carrying out this study made it possible toobservethat there is a highly significant influence in the speech of the inhabitants of that townfromthe relationships they maintain with the rural setting. The words indicated as belongingtorural vocabulary by Souza (2008), Ribeiro (2010), Freitas (2012), Cordeiro (2013), Miranda(2015) were found in the Claudian dialect.